2010
DOI: 10.2298/sarh1002011a
|View full text |Cite
|
Sign up to set email alerts
|

The use of platelet-rich fibrin membrane in gingival recession treatment

Abstract: Results of this study confirm both procedures as effective with equivalence of clinical results in solving gingival recession problems. The utilization of the PRF resulted in a decreased postoperative discomfort and advanced tissue healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
5
35
1
Order By: Relevance
“…Study design and patient features: Ten RCTs [31][32][33][34][35][36][37][38][39][40] were included as shown in Table 1. The age of the participants ranged from 18 to 52 years with a follow-up period ranging from 6 to 12 months.…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Study design and patient features: Ten RCTs [31][32][33][34][35][36][37][38][39][40] were included as shown in Table 1. The age of the participants ranged from 18 to 52 years with a follow-up period ranging from 6 to 12 months.…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
“…The age of the participants ranged from 18 to 52 years with a follow-up period ranging from 6 to 12 months. Four included studies compared PRF in conjunction with CAF (PRF + CAF) to CAF alone (CAF) [31,33,36,40] while other four studies compared PRF + CAF to CAF in conjunction with CTG (CAF + CTG) [34,35,37,39]. One study assessed the effect of the addition of PRF to CAF in conjunction to CTG (PRF + CTG + CAF) and compared the results with CAF + CTG [32].…”
Section: Features Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…What is also important is that the resulting from the patient clot contains no chemical or biological additives while it has a solid structure and can easily be used to prepare strong, elastic fibrin membrane. Many publications with promising results appeared in the past few years about the treatment of gingival recessions with PRF [6,[12][13][14][15] . In 2011 Zadeh H H [16] modified the tunnel technique offering the so-called VISTA (Vestibular Incision subperiosteal Tunnel Access) technique for the treatment of multiple adjacent gingival recessions in the front part of the maxilla.…”
Section: Introductionmentioning
confidence: 99%
“…9 PRF, providing several advantages including supporting wound healing, bone growth, maturation, graft stabilization, wound closure and homeostasis, is utilized to provide high concentrated growth factors to the bone defect areas. 10 Aleksic et al 11,12 concluded that the use of PRF and SCTG are equally effective in GR treatment. Furthermore, the authors stated that the use of PRF resulted in reduced post-operative discomfort and improved tissue healing.…”
Section: Discussionmentioning
confidence: 99%